The clinical utility of newer antidepressant agents: Understanding the role in management of MDD - Kristin Waters, PharmD, BCPS, BCPP (American Association of Psychiatric Pharmacists, 2022)
Whereas MDD is characterized in part by changes in mood, other symptoms can also cause significant impairment, including sexual dysfunction, cognitive impairment, and fatigue. Newer antidepressants are explored with the goal of more optimally treating these non-mood-related symptoms of MDD. The 3 oral antidepressants that have been FDA-approved most recently include vortioxetine, vilazodone, and levomilnacipran. Unique features of these antidepressants are explored through 3 patient cases.